Overcoming Blood-Brain Barrier Resistance: Implications for Extracellular Vesicle-Mediated Drug Brain Delivery - Dardet, Jean Paul; Serrano, Nelson; András, Ibolya Edit; Toborek, Michal (Frontiers in Drug Delivery, 2022)
Drug delivery across the blood-brain barrier (BBB) has several challenges, especially towards targeting neurological diseases, due to tight and selective barrier function of the BBB. Several structural and functional components of this barrier contribute to restricting drug entry, such as tight interendothelial junctions, efflux transporters, drug metabolizing enzymes, and crosstalk between cells of the neurovascular unit. Among different strategies to overcome BBB resistance to therapeutic drug delivery, the use of extracellular vesicles (EVs) gained attention in recent years. This review discusses the BBB structural and functional resistance, as well as potential avenues to overcome this challenge using EVs as drug delivery vehicles into the brain.